Diseño de una Guía Metodológica de gestión de actores para proyectos de formulación de presupuestos participativos en entidades del orden territorial en Colombia. (2017)
The present research results in the design of the Methodological Guide for the management of actors for participatory budgeting projects in entities of the territorial order in Colombia, a research work was carried out under a methodological approach of qualitative descriptive type, where they were defined, Where a sequence of phases was defined, which resulted in a strategic tool that facilitates the systematization and accompaniment of the process developed in the management of actors within the framework of the projects focused on defining which projects will be allocated the resources available in the public administrations by participatory budgeting , In order to strengthen mechanisms for citizen participation in public investment projects.